ICT and inclusive education: Attitudes of the teachers in secondary education - Jose Maria Fernandez-Batanero; Maria Jesus Colmenero-Ruiz (OmniaScience, 2016)
<span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The inclusion and the Information and Communication Technologies (ICT) configure a field of great scientific interest in the current society. In this context, the attitudes of the teachers towards the ICT play an important role. The present article gathers the results of a study whose purpose was to determine how a teacher will use and integrate the 'Information and Communication Technologies' (ICT) in inclusive classrooms. This will also identify the factors that promote good educational practices supported by ICT. Towards this we prepared a case study of multiple cases. The questionnaire and group discussion are the techniques that are used for collecting required information. To validate the questionnaire, it was used the expert judgment method selected by the "Coefficient expert Competence" procedure or also named "K coefficient". The Reliability was established by Cronbach's Alfa method with a value of 0.87. The result shows that teachers in general have a positive attitude towards ICT, especially the male teachers with greater possibilities of interaction with ICT. This will also promote inclusive and cultures policies between networks of schools and it is presented as an important factor in developing good educational practice with the support of ICT.